Bali's cultural festivals: A visitor magnet supporting sustainable tourism - Yanti, Ni Kadek Winda; Mahadewi, Ni Nyoman Tri; Wisudawati, Ni Nyoman Sri; Shantika, Budi; Yusnny, Bella Desita (International Journal of Applied Sciences in Tourism and Events, 2025)
This study aims to further understand the perceptions of visitors to the Cultural Festival towards strengthening Balinese cultural identity. Cultural festivals in Bali are held with the aim of maintaining, preserving and as exposure of cultural values to the wider public. Cultural Festival activities in Bali organized by the government such as the Bali Arts Festival, Denpasar Festival and the latest is the Kesanga Festival. In organizing each festival, the principle of sustainability is one of the strong foundations for maintaining social, economic and environmental values without distorting local traditions and culture. This study uses quantitative data that is described descriptively. The unstructured interview was conducted during the data collection with informants from the representative of the festivals’ social media associates. The data in this study were collected using a questionnaire distribution technique. The number of samples in this study was 100 respondents calculated using the Slovin formula with a 90% confidence level and a 10% error rate with no specific criteria yet mainly has experience in visiting (visitor) one of the cultural event used as research object. The results of the study showed that the variables of marketing strategy, cultural experience, cultural authenticity, and sustainability practices play an important role in creating strengthening cultural identity at cultural festivals in Bali.